2017
DOI: 10.1093/cid/cix151
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Clinical Practice of Using the Xpert MTB/RIF Assay in Thailand

Abstract: Background. Delayed diagnosis of tuberculosis (TB) and drug-resistant TB are major challenges of TB control in Thailand. This study assessed the practicality of the Xpert MTB/RIF assay in a real-life setting with high prevalence of human immunodeficiency virus (HIV) infection and pulmonary tuberculosis (PTB).Methods. This prospective study was conducted at 3 large tertiary care hospitals. Patients who had suspected PTB were enrolled into the study. Expectorated sputum samples were sent for staining, mycobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
0
14
5
2
Order By: Relevance
“…The difference could be a constellation of many factors including the nature of collected specimens (spot versus morning), geographical distribution of study sites which were distant from the reference laboratory and the sputum manipulation procedures done (processed versus un processed samples). The sensitivity obtained in this study is also lower than the findings from a study done in Thailand which showed a sensitivity of 81% among culture positive, smear negative patients [ 33 ]. The Thailand study was however done on a small sample size of 494 patients.…”
Section: Discussioncontrasting
confidence: 94%
“…The difference could be a constellation of many factors including the nature of collected specimens (spot versus morning), geographical distribution of study sites which were distant from the reference laboratory and the sputum manipulation procedures done (processed versus un processed samples). The sensitivity obtained in this study is also lower than the findings from a study done in Thailand which showed a sensitivity of 81% among culture positive, smear negative patients [ 33 ]. The Thailand study was however done on a small sample size of 494 patients.…”
Section: Discussioncontrasting
confidence: 94%
“…Eleven studies (4196 participants) reported a higher percentage (> 25%) of participants with a history of tuberculosis ( Adelman 2015 ; Al‐Darraji 2013 ; Boehme 2010 ; Kawkitinarong 2017 ; Ko 2016 ; Lawn 2011 ; Mutingwende 2015 ; O'Donnell 2015 ; Reddy 2017 ; Reechaipichitkul 2017 ; Theron 2011 ) and 16 studies (8205 participants) reported a lower percentage (≤ 25%) of participants with a history of tuberculosis ( Balcha 2014 ; Barmankulova 2015 ; Bates 2013a ; Bjerrum 2016 ; Boehme 2010 ; Boum 2016 ; Carriquiry 2012 ; Dorman 2018 ; Hanrahan 2013 ; Helb 2010 ; LaCourse 2016 ; Luetkemeyer 2016 ; Mbelele 2017 ; Scott 2017 ; Sohn 2014 ; Yoon 2017 ). In studies with a higher percentage of participants with previous tuberculosis, Xpert MTB/RIF pooled sensitivity (95% CrI) was 86% (82% to 89%), similar to the pooled sensitivity of 85% (81% to 89%) in studies with a lower percentage of participants with previous tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…We included 70 studies involving 37,237 unselected participants (Adelman 2015; Al‐Darraji 2013; Atwebembeire 2016; Balcells 2012; Balcha 2014; Barmankulova 2015; Bates 2013a; Bjerrum 2016; Boehme 2010; Boehme 2011; Boum 2016; Calligaro 2015; Calligaro 2017; Carriquiry 2012; Chaisson 2014; Chen 2017; Chew 2016; Cowan 2017; Davis 2014; Dorman 2018; Geleta 2015; Hanif 2011; Hanrahan 2013; Hanrahan 2014; Helb 2010; Henostroza 2016; Huang 2015; Huh 2014; Kawkitinarong 2017; Kim CH 2015; Ko 2016; Kurbaniyazova 2017; Kurbatova 2013; Kwak 2013; LaCourse 2016; Lawn 2011; Lippincott 2014; Liu 2017; Luetkemeyer 2016; Mbelele 2017; Mollel 2017; Moussa 2016; Mutingwende 2015; Ngabonziza 2016; Nikam 2014; Nliwasa 2016; Nosova 2013a; O'Donnell 2015; Park 2013; Pinyopornpanish 2015; Rachow 2011; Reddy 2017; Reechaipichitkul 2017; Rice 2017; Safianowska 2012; Sah 2017; Scott 2011; Scott 2017; Shao 2017; Sharma 2015; Shenai 2016…”
Section: Resultsmentioning
confidence: 99%
“…(15) tarafından 2010-2013 yılları arasında, akciğer tüberkülozu tanılı hastalarda Xpert MTB/RIF ile yapılmış 22 çalışmanın metaanalizi sonucu, bu sistemin, yayma mikroskobisi sonuçları göz önüne alınmaksızın yapılan duyarlılık tahminlerinin %58-100; özgüllük tahminlerinin %86-100 arasında değiştiği, fakat kümelenmenin duyarlılık için %89 ve özgüllük için %99 civarında olduğu bildirilmiştir. Bununla birlikte, sistemin onay aldığı tarihten bu yana yöntem performanslarının karşılaştırıldığı çalışmalarda, kesin TB tanısı ya yalnızca kültür sonuçları baz alınarak (16)(17)(18) ya da klinik/radyolojik ve laboratuvar sonuçları birlikte değerlendirilerek (19,20) konulduğundan, birbirinden çok farklı sonuçlar elde edilebilmiştir. Örneklerin solunum ya da solunum dışı olması ve yayma pozitif veya negatif olması da perfomans yüzdelerini etkilemiştir.…”
Section: Id Id Idunclassified
“…Geleta DA ve ark. (16) MGIT (19) çalışmasında yayma pozitif ve negatif, kültür-pozitif balgam örnekleri için Xpert MTB/RIF'in duyarlılık değerlerini sırasıyla %100 ve %81 olarak saptanmıştır. Ayrıca kültür negatif fakat klinik olarak TB olduğu kabul edilen hastalarda Xpert MTB/RIF'in duyarlılık ve pozitif prediktif değerleri %37.8 ve %83.8 olarak belirlenmiştir.…”
Section: Id Id Idunclassified